2020
DOI: 10.1177/0960327120958037
|View full text |Cite
|
Sign up to set email alerts
|

Possible mechanism of bamboo shoots (Bambusa balcooa) induced thyroid disruption – An in vitro study

Abstract: Endemic goitre and associated iodine deficiency disorders (IDDs) are a major concern in public health even in the period of post salt iodization in many regions. Among others the consumption of cyanogenic plants found responsible for the persistence of such diseases. Bamboo shoots (BS) is one such cyanogenic plant food that caused disruption of certain thyroid hormone synthesizing regulatory element as has already been reported in our earlier study. In this investigation the possible mechanism of thyrocytes di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…Additionally, the in vitro study of Sarkar et al, showed that cyanogenic constituents in bamboo shoots generate reactive oxidative species that contribute to oxidative DNA damage and cell cycle disruption. This is followed by the inhibition of regulatory elements that synthesize thyroid hormones [ 138 , 139 ].…”
Section: Environmental Factors That Influence Tsh and Thyroid Hormone Levelsmentioning
confidence: 99%
“…Additionally, the in vitro study of Sarkar et al, showed that cyanogenic constituents in bamboo shoots generate reactive oxidative species that contribute to oxidative DNA damage and cell cycle disruption. This is followed by the inhibition of regulatory elements that synthesize thyroid hormones [ 138 , 139 ].…”
Section: Environmental Factors That Influence Tsh and Thyroid Hormone Levelsmentioning
confidence: 99%
“…(ii) children's maximal levels of TSH and FT 3 in Unakoti where BS consumption was highest and iodine intake was adequate (Table 1) -suggests that BS might have interfered with thyroid function in studied children. However, it has already been reported that the antithyroidal action of BS can be mitigated partially by iodine [49,51].…”
Section: Thyroid Gland and Its Relation With Age And Ftmentioning
confidence: 99%
“…However, although previous studies indicated that the co-exposure to perchlorate and thiocyanate is potentially deleterious to the thyroid function in adults and in susceptible individuals, as pregnant women, fetus, and newborns, the effects of thiocyanate per se in the thyroid are still controversial in humans (27,30,31,76) Finally, the molecular mechanisms involved in the thiocyanate regulation of thyroid function are not completely understood. Studies using primary thyroid cells cultures exposed to plant extracts rich in thiocyanate demonstrated an increased production of reactive oxygen species, induced cell injury and DNA damage, decreased gene expression and activity of proteins involved in the synthesis of thyroid hormones (77,78). However, the direct effects of thiocyanate per se in the thyrocytes have never been reported.…”
Section: Thiocyanatementioning
confidence: 99%